Social Studies Teacher Candidates' Views on Historic Environment Education - (:unkn) unknown (MARMARA UNIV, 2017)
In this study, it is aimed to determine the opinions of Social Studies teacher candidates on historic environment education. Based on this aim, the data were collected through semi-structured interviews within the scope of qualitative research methodology. Participants of the research were eight students who studied in Bulut University (nickname) Education Faculty Social Sciences Teacher Education Department in 2011-2012 academic year. The collected data were analyzed by descriptive analysis method. According to the results obtained from the research, the teacher candidates' historic environment sensitivities are quite high. However, according to the prospective teachers, both in Social Studies Curriculum and historic environment education they have taken during undergraduate study are insufficient in Turkey.
Keywords: Historic environment; historic environment education; teacher candidate; Social Studies education